Care handover to chronic conditions to regionalized planning - Kamila da Silva Pena; Rosane Machado Rollo; Camila Luana Oliveira Reuter; Vilma Constancia Fioravante dos Santos; Deise Lisboa Riquinho; Adriana Roese Ramos (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To analyze the possibilities of the transition from care to the problem of chronic illness due to the need of regionalized municipal planning. Method: An exploratory qualitative study was carried out in one of the Health Regions of Rio Grande do Sul, together with the Primary Health Care Coordinators. Results: The final thematic categories that emerged from the results were: "The relationship between municipalities of the Health Region and health planning", Organizational flow of care of users with chronic diseases", and "Managing care in the health system: meeting the demands of chronically sick users". Conclusions: The scenario under study demonstrates the persistence of barriers that affect health care for NCDs, such as the scarcity of investments, lack of planning and disarticulation of communication among municipalities. These conditions reflect on the path of the user among the health services, weakening the transition process of care.